TENDER PROYEK PEMBANGUNAN JALAN AKSES BANDAR UDARA SIBISA, SUMATERA UTARA BERDASARKAN HUKUM PERSAINGAN USAHA - Tara Damayanti; Sharda Abrianti (Reformasi Hukum Trisakti, 2022)
In its ruling on Case Number 18/KPPUI/2018, the Business Competition Supervisory Commission (KPPU) found a violation of Article 22 of Law Number 5 of 1999 regarding Bidding for the Construction of the Access Road for Sibisa Airport in North Sumatra Province. The Medan District Court incorrectly upheld the KPPU's ruling in ruling Number 681/Pdt.Sus.KPPU/2019/PN-Mdn. The primary issue in this study is to examine how to choose the winning bid for the construction of the Sibisa airport access road in North Sumatra and whether the decision regarding bid rigging for the construction of the Sibisa North Sumatra airport access road is in compliance with Article 22 of Law Number 5 of 1999 prohibiting monopolistic practices and unfair business practices. he type of research chosen by the author is normative legal research with the nature of descriptive research using secondary data. The results of the study were analyzed qualitatively by using a deductive conclusion. The conclusion of this research is in the process of determining the winning tender for the construction project of the Sibisa airport access road, North Sumatra.